THE EVOLUTION OF DISCONTENT: ANGRY YOUNG MEN LITERATURE IN THE 21ST CENTURY - Chinakov Abdulahad Mo‘minjon ugli (TADQIQOTLAR, 2025)
Abstract The "Angry Young Men" literary movement emerged in mid-20th century Britain, representing a generation’s discontent with post-war socio-political realities. This study investigates how the themes of alienation, rebellion, and frustration have evolved in 21st-century literature. Focusing on contemporary authors such as Mohsin Hamid, Aravind Adiga, Dave Eggers, and Ocean Vuong, the research compares modern works with the classics of Osborne and Amis. The study reveals that while the socio-political context has shifted, core themes of class conflict, technological alienation, and identity struggles persist. Furthermore, modern literary techniques, such as multivocal narratives and nonlinear storytelling, enhance the relevance and inclusivity of the Angry Young Men tradition in a globalized, digital world.